A four‐step control for IGBT switching improvement using an active voltage gate driver. Issue 6 (2nd February 2022) - Li, Chen; Tan, Kun; Ji, Bing; Wang, Zhiqiang; Ding, Shuai; Lefley, Paul
Abstract: Gate drivers form an essential interface between the high power transistors and low voltage control circuits in power converters to govern the transistor switching operations and maintain other ancillary functions. A sophisticated gate driver with a segmented drive booster allows optimized trajectories to be staged out during switching transitions, which provides an extended degree of control freedom at the device level. This helps to improve the trade‐offs between multifaceted parameters such as switching losses, overshoots, ringing, and electromagnetic interference, parasitic turn‐on fault, etc. In this paper, a digitalized active gate driver with segmented voltage control is designed and experimentally verified, which is capable of shaping the dynamic switching waveforms of Insulated Gate Bipolar Transistors (IGBT) using a four‐step gate control method. Compared to the traditional constant voltage gate driver method and the three‐step segmented method, the proposed four‐step AVGD control demonstrates reductions of the IGBT turn‐on current overshoot and suppressions of the voltage overshoot on the complementary freewheeling diode without sacrificing its turn‐on switching losses.